English Education Department Students’ Difficulties in Translating English News Report - Nurlaila Nurlaila; Andi Irlina (Institut Agama Islam Negeri Madura, 2021)
Different language systems between English and Indonesian cause difficulties in communication, both written and oral. This case can be solved with translation. This research aims to find about types of translation difficulties in translating English news reports encountered by the fourth semester of English Education Department students of Tarbiyah and Teacher Training Faculty at UIN Antasari Banjarmasin. This research is a qualitative descriptive research by analyzing the text of the news report entitled